Ultrahigh molecular weight polyethylene fiber as well as preparation method and application thereof

By adding nanomagnetic particles during spinning and performing thermal drafting in the magnetic field, the cross-linking degree of ultra-high molecular weight polyethylene fiber is improved, and the problem of insufficient creep resistance and strength of fibers is solved, achieving efficient resistance Creep performance and tensile fracture strength are improved.

CN119162683APending Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310737779.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The creep resistance and strength of ultra-high molecular weight polyethylene fibers need to be improved, and the existing technology methods are not effective, limiting their application in military and civilian industries.

Method used

Nanomagnetic particles are added during the spinning process and thermal drafting is performed in the magnetic field to control the crosslinking degree of fibers to be greater than or equal to 84.5 wt.% to improve the creep resistance and tensile fracture strength of the fibers.

Benefits of technology

The creep resistance and tensile breaking strength of the fiber are significantly improved, so that the creep elongation of the fiber at 50℃ is less than or equal to 2%, the tensile breaking strength is greater than 350N/tex, and both have high tensile strength and Advantages of creep resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162683A_ABST
    Figure CN119162683A_ABST
Patent Text Reader

Abstract

The invention relates to a polyethylene fiber, and discloses an ultra-high molecular weight polyethylene fiber as well as a preparation method and application thereof. The fiber contains nano magnetic particles, and the crosslinking degree of the fiber is greater than or equal to 84.5 wt.%. The preparation method comprises the following steps: (1) spinning an ultra-high molecular weight polyethylene raw material in the presence of an auxiliary agent and a solvent to obtain primary gel silk; the auxiliary agent contains nano magnetic particles, a coupling agent and an initiator; and (2) removing the solvent from the primary gel silk, and carrying out hot drawing treatment in a magnetic field. The ultra-high molecular weight polyethylene fiber has the advantages of high breaking tensile strength and good creep resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polyethylene fiber, in particular to an ultra-high molecular weight polyethylene fiber and a preparation method and application thereof. Background Art

[0002] As one of the three major high-performance fibers in the world, ultra-high molecular weight polyethylene (UHMWPE) fiber has many excellent properties. Due to its high specific strength, high specific modulus, excellent impact resistance and good wear resistance, UHMWPE fiber can also withstand corrosion from strong acids, strong alkalis and other chemicals, has a high electromagnetic wave transmittance, and a lower friction coefficient than many materials. It has the characteristics of non-absorption of water and good biocompatibility. Therefore, UHMWPE fiber is widely used in many fields such as military protective materials, aerospace related materials, medical materials, radar antenna covers, and marine anchor ropes. Although UHMWPE fiber has many excellent properties, this material also has some defects, such as poor heat resistance, poor creep resistance, poor composite bonding, and high melt viscosity, which makes processing and molding difficult. Among them, creep is one of the main problems of organic fibers. Due to the poor creep resistance of material molecules and low Young's modulus, the material molecules will slip between molecules when subjected to force, resulting in poor creep resistance of the fiber; the creep property of UHMWPE fiber greatly limits its application in military and civilian industries.

[0003] Currently, there are two main methods to improve the creep resistance of UHMWPE fibers. The first is to add nanoparticles, which can improve the creep resistance to a certain extent, but the effect is not good. The second is to add a cross-linking agent during the spinning process to induce cross-linking between the molecular chains inside the fiber, reduce the slippage between the molecular chains to improve the creep resistance, but this method has a poor cross-linking effect and the improvement in creep resistance is not very obvious.

[0004] CN103993479A discloses a method for preparing a silane cross-linked modified ultra-high molecular weight polyethylene fiber, comprising: placing an ultra-high molecular weight polyethylene UHMWPE gel fiber that has not been dried in a modification solution containing an initiator and a silane coupling agent, ultrasonically treating it, and then performing multi-stage (three-stage) thermal stretching to obtain a modified fiber. However, the modified fiber obtained by this method has a low creep resistance, but its strength needs to be improved, which is not conducive to later applications. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that the creep resistance and strength of ultra-high molecular weight polyethylene fibers in the prior art need to be improved, and to provide an ultra-high molecular weight polyethylene fiber and a preparation method and application thereof.

[0006] The inventor of the present invention unexpectedly discovered in the research that by adding magnetic nanoparticles to ultra-high molecular weight polyethylene fibers and controlling the crosslinking degree of the ultra-high molecular weight polyethylene fibers to be greater than or equal to 84.5wt.%, the creep elongation of the fibers at 50°C can be less than or equal to 2%, and the tensile strength at break is greater than 350N / tex, so that the ultra-high molecular weight polyethylene fibers can have the advantages of high tensile strength at break and good creep resistance. Based on the above findings, the present invention is proposed.

[0007] In order to achieve the above object, the present invention provides an ultra-high molecular weight polyethylene fiber, which contains nano-magnetic particles and has a cross-linking degree greater than or equal to 84.5wt.%.

[0008] A second aspect of the present invention provides a method for preparing an ultra-high molecular weight polyethylene fiber, comprising the following steps:

[0009] (1) spinning an ultra-high molecular weight polyethylene raw material in the presence of an additive and a solvent to obtain primary jelly filaments;

[0010] The auxiliary agent contains nano magnetic particles, a coupling agent and an initiator;

[0011] (2) After removing the solvent from the primary jelly filaments, they are subjected to a heat drawing treatment in a magnetic field.

[0012] The third aspect of the present invention provides an application of the ultra-high molecular weight polyethylene fiber provided in the first aspect or the ultra-high molecular weight polyethylene fiber prepared by the preparation method provided in the second aspect in textiles.

[0013] Through the above technical scheme, the ultra-high molecular weight polyethylene fiber contains magnetic nanoparticles, and the crosslinking degree of the ultra-high molecular weight polyethylene fiber is controlled to be greater than or equal to 84.5wt.%, which can make the creep elongation of the fiber at 50°C less than or equal to 2%, and the tensile breaking strength greater than 350N / tex, so that the ultra-high molecular weight polyethylene fiber can have the advantages of high tensile strength at break and good creep resistance.

[0014] The preparation method provided by the present invention can improve the chemical bonding effect of the coupling agent and the ultra-high molecular weight polyethylene fiber through the synergistic effect of the nano-magnetic particles and the magnetic field and the initiator, thereby effectively improving the cross-linking effect of the ultra-high molecular weight polyethylene fiber, and further significantly improving the creep resistance and tensile strength of the ultra-high molecular weight polyethylene fiber, so that the creep elongation of the prepared fiber at 50°C is less than or equal to 2%, the tensile strength is greater than 350N / tex, and the fiber performance is stable for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1The electron microscope images of the ultra-high molecular weight polyethylene fibers obtained in Example 1 and Comparative Example 3 of the present invention magnified 500 times;

[0016] Figure 2 This is a comparison chart of the creep elongation of the ultra-high molecular weight polyethylene fibers obtained in Example 1 and Comparative Example 3 tested by the hanging weight method of the present invention (the test environment temperature is 50° C.). DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] As mentioned above, the first aspect of the present invention provides an ultra-high molecular weight polyethylene fiber, wherein the fiber contains nano-magnetic particles, and the degree of cross-linking of the fiber is greater than or equal to 84.5 wt.%.

[0019] According to the present invention, ultra-high molecular weight polyethylene refers to polyethylene with a molecular weight of more than 1 million. Preferably, the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 8 million. More preferably, the density of the ultra-high molecular weight polyethylene is 0.97 to 0.98 g / cm 3 The ultra-high molecular weight polyethylene fiber was dissolved in decahydronaphthalene at 120-140°C, and the solid phase was obtained after filtration. The magnetization intensity (saturation magnetization intensity) of the solid phase at 298K was measured by Lake Shore-7400 vibrating sample magnetometer at a maximum magnetic field intensity of 1KOe. When the magnetization intensity obtained was greater than or equal to 5emu / g, it was indicated that the solid phase contained magnetism. The obtained solid phase was dispersed with water and subjected to particle size analysis to determine the particle size of the particles in the solid phase.

[0020] According to the present invention, the degree of crosslinking is measured by the method mentioned in GB / T 18474-2001.

[0021] The ultra-high molecular weight polyethylene fiber provided by the present invention contains nano-magnetic particles, and its cross-linking degree is controlled to be greater than or equal to 84.5wt.%, which can make the creep elongation of the fiber at 50°C less than or equal to 2%, and the tensile strength at break greater than 350N / tex, so that the ultra-high molecular weight polyethylene fiber can have the advantages of high tensile strength at break and good creep resistance. And the fiber has a high breaking tensile force of 33.8-160N. The use strength can be guaranteed during use, and it is not easy to deform and break during high-temperature cleaning or high-temperature drying, thereby extending the service life.

[0022] Generally, the higher the temperature, the worse the creep resistance of the fiber, that is, at higher temperatures, the creep resistance of the fiber will deteriorate. According to the present invention, the creep elongation is measured by the hanging weight method, and a 1.5m long parallel fiber is placed in an environmental chamber for creep performance testing, the hanging weight is 20% of the single fiber breaking strength, the hanging time is 48h, and the test temperature is 50°C, that is, the creep elongation of the fiber is less than or equal to 2% when the hanging weight is 20% of the single fiber breaking strength and the temperature is 50°C. The tensile breaking strength is obtained by GB / T 14344-2008 test. The breaking tension of the fiber is measured by GB / T14337-2008.

[0023] Preferably, the crosslinking degree of the fiber is 84.5-97.5wt.%. More preferably, the crosslinking degree of the fiber is 85-93wt.%, in which case the creep elongation of the obtained fiber at 50°C is less than or equal to 1.8%, the tensile strength at break is 358-370N / tex, and the breaking force is 35-40N.

[0024] Preferably, the fiber fineness is less than or equal to 150D. The fiber is more suitable for textiles, and can facilitate subsequent weaving of the fiber, so that the produced textile is more comfortable. Further preferably, the fiber fineness is less than or equal to 100D.

[0025] According to the present invention, the fiber density is detected by GB / T14335, the fiber length is detected by GB / T14336, and the fiber fineness is calculated by the detected density and length.

[0026] Preferably, the content of the nanomagnetic particles in the fiber is 1-5wt.%. The fiber contains the above-mentioned content of nanomagnetic ions, which can further improve the creep resistance and tensile strength of the fiber. Specifically, a fixed mass of ultra-high molecular weight polyethylene fiber is dissolved by decalin at 120-140°C, a solid phase is obtained after filtration, and the fixed phase is weighed after drying. The content of the nanomagnetic particles in the fiber is calculated by the mass of the solid phase and the added ultra-high molecular weight polyethylene fiber. Further preferably, the content of the nanomagnetic particles in the fiber is 1-2.5wt.%.

[0027] Preferably, the particle size of the nanomagnetic particles is 50-200 nm. Further preferably, the particle size of the nanomagnetic particles is 50-120 nm. Under this condition, the nanomagnetic particles are more evenly dispersed in the fiber, which can improve the crosslinking degree of the fiber, so that the prepared fiber has better creep resistance and higher tensile strength.

[0028] Preferably, the magnetization intensity of the nanomagnetic particles is 20-50emu / g. Limiting the magnetization intensity of the nanomagnetic particles within the above range can further improve the creep resistance and tensile strength of the fiber. In order to further improve the creep resistance and tensile strength of the fiber, it is further preferred that the nanomagnetic particles are selected from at least one of manganese-zinc ferrite, ferroferric oxide and magnetic polystyrene.

[0029] Among them, on the basis of confirming the presence of nanomagnetic particles, the nanomagnetic particles containing metal elements are qualitatively identified by element detection (which can be detected by flame atomic absorption spectrophotometer), and the specific selection of nanomagnetic particles without metal ions can also be qualitatively identified by infrared detection.

[0030] A second aspect of the present invention provides a method for preparing an ultra-high molecular weight polyethylene fiber, comprising the following steps:

[0031] (1) spinning an ultra-high molecular weight polyethylene raw material in the presence of an additive and a solvent to obtain primary jelly filaments;

[0032] The auxiliary agent contains nano magnetic particles, a coupling agent and an initiator;

[0033] (2) After removing the solvent from the primary jelly filaments, they are subjected to a heat drawing treatment in a magnetic field.

[0034] According to the present invention, the ultra-high molecular weight polyethylene raw material can be purchased from a commercial source or prepared by oneself. The ultra-high molecular weight polyethylene raw material can be a powder or a granular raw material, preferably a powder.

[0035] The inventor found in the research process that the synergistic effect of nanomagnetic particles and magnetic field and initiator can improve the chemical bonding effect of coupling agent and ultra-high molecular weight polyethylene fiber, thereby effectively improving the cross-linking effect of ultra-high molecular weight polyethylene fiber, and then significantly improving the creep resistance and tensile strength of ultra-high molecular weight polyethylene fiber, and the fiber performance is long-term stable. Moreover, in the prior art CN103993479A, the creep resistance of ultra-high molecular weight polyethylene fiber is changed by combining initiator and coupling agent, but the three-stage stretching method is adopted in the scheme, the stretching number is large, the labor cost and mechanical operation cost are relatively high, and the possibility of multiple stretching failures will also increase. In the present invention, only nanomagnetic particles need to be added to ensure its creep resistance while reducing the stretching number, and the tensile strength of the fiber can also be greatly improved.

[0036] Preferably, the step (1) comprises: S1 mixing an ultra-high molecular weight polyethylene raw material, a solvent and nano-magnetic particles to obtain a suspension; S2 mixing the suspension with an initiator, a coupling agent and a solvent and spinning them to obtain primary jelly filaments.

[0037] According to the present invention, in order to improve the dissolution effect of ultra-high molecular weight polyethylene raw material and initiator and coupling agent in the solvent, the solvent used in step S1 may be different from the solvent used in step S2, so the solvent in step S1 is recorded as solvent I, and the solvent in step S2 is recorded as solvent II.

[0038] The nano-magnetic particles are first mixed with ultra-high molecular weight polyethylene raw materials to form a suspension, and then mixed with an initiator and a coupling agent for coupling, which can improve the dispersion effect of the nano-magnetic particles in the ultra-high molecular weight polyethylene and improve its creep resistance and tensile strength.

[0039] Preferably, in step (1), the auxiliary agent further comprises a solubilizer, which is added in step S1. The addition of the solubilizer can reduce the fiber fineness while improving the high creep resistance and high tensile strength of the fiber. Further preferably, the addition amount of the solubilizer is 1-10 g relative to 100 g of the ultra-high molecular weight polyethylene raw material.

[0040] Preferably, in step (1), relative to 100g of the ultra-high molecular weight polyethylene raw material, the amount of the nano-magnetic particles added is 1-10g, specifically 1g, 2.5g, 5g, 7.5g, 10g, or any value between these values; the amount of the initiator added is 1-35g, specifically 1g, 10g, 20g, 30g, 35g, or any value between these values; the amount of the coupling agent added is 1-35g, specifically 1g, 10g, 20g, 30g, 35g, or any value between these values. In the case of the above mass ratio, the coordination effect between the magnetic nanoparticles, the initiator and the coupling agent is better, thereby further improving the creep resistance and tensile strength of the ultra-high molecular weight polyethylene fiber.

[0041] Preferably, the magnetization intensity of the nanomagnetic particles is 20-50emu / g, specifically 20emu / g, 30emu / g, 40emu / g, 50emu / g, or any value between these values. Further preferably, the nanomagnetic particles are selected from at least one of manganese zinc ferrite, ferroferric oxide and magnetic polystyrene. Specifically, manganese zinc ferrite can be added in the form of nanocrystals, and magnetic polystyrene can be added in the form of nanospheres. The above-mentioned nanomagnetic particles have a better effect with the initiator, coupling agent and magnetic field, thereby further improving the creep resistance and tensile strength of the obtained ultra-high molecular weight polyethylene fiber.

[0042] Preferably, the solubilizer is selected from at least one of polyethylene glycol, sodium xylene sulfonate, sodium p-toluene sulfonate, polysorbate and ethanol. The selection of the above solubilizer can further improve the swelling effect of the ultra-high molecular weight polyethylene fiber powder, and can further reduce the fiber fineness while ensuring high creep resistance and high tensile strength.

[0043] Preferably, in step S1, the solvent I is selected from at least one of paraffin oil, mineral oil, decalin, tetralin and xylene; limiting the solvent I to the above range can improve the dispersion effect of the ultra-high molecular weight polyethylene raw material in the solvent I, thereby improving the spinning efficiency and making the prepared fiber more uniform. Preferably, the solvent I may also contain a small amount of ethanol. According to the present invention, the amount of solvent I added is 2-150g.

[0044] The mixing time can be determined by the test personnel according to the actual situation, and it is only necessary to fully swell the ultra-high molecular weight polyethylene fiber powder. Preferably, in step S1, the mixing conditions at least include: the mixing time is 3-24 hours.

[0045] Preferably, the organic initiator is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide and diisopropyl peroxydicarbonate; the coupling agent is selected from at least one of vinyl silane, organic titanate and acryloxy silane. The above-defined initiators and coupling agents have better effects, and can further improve the creep resistance and tensile strength of the fiber.

[0046] In order to further improve the tensile strength and creep resistance of the fiber, preferably, in step S1, pre-stretching is further included after spinning, and the pre-stretching conditions include at least: a stretching ratio of 3-6 times.

[0047] According to the present invention, the mixing in step S2 is carried out in a screw extruder, which can be a single screw extruder or a twin screw extruder. Preferably, the screw extruder is a twin screw extruder, more preferably a pressurized twin screw extruder. Preferably, the mixed solution of the initiator, the coupling agent and the solvent II is added by a metering pump.

[0048] According to the present invention, in step S2, pre-stretching can be achieved by any machine or structure capable of achieving pre-stretching. Preferably, pre-stretching is achieved by a spinneret and a spinning box. Preferably, the method further comprises cooling the material obtained after the pre-stretching treatment. The cooling treatment can be carried out under any feasible conditions. As a specific embodiment of the present invention, the cooling treatment is carried out in a cooling water bath. Specifically, the conditions for the cooling treatment include: a temperature of 0-20°C and a time of 3-10s.

[0049] According to the present invention, in step S2, the solvent II may be at least one of paraffin oil, ethylene glycol and mineral oil. Preferably, the solvent II is paraffin oil.

[0050] Preferably, in step (2), the conditions of the magnetic field treatment at least include: the magnetic field induction intensity is 100-800 A / m; the conditions of the heat drawing treatment at least include: the temperature is 120-180°C, the relative humidity is 20-80%, and the stretching ratio is 8-20 times. The fiber prepared under the above conditions has a finer diameter, higher tensile breaking strength and creep resistance.

[0051] According to the present invention, in step (2), desolventizing can be achieved in any feasible manner. Preferably, desolventizing is achieved by extraction with an extracting liquid and drying. The selection of the extracting liquid, the extraction conditions and the drying conditions can be determined by those skilled in the art according to actual conditions.

[0052] According to the present invention, the amount of solvent II added can be determined by the experimenter according to the actual situation. As a specific embodiment of the present invention, relative to 100g of ultra-high molecular weight polyethylene raw material, the amount of solvent II added is 20-140g, specifically 20g, 40g, 60g, 80g, 100g, 120g, 140g, or any value between these values.

[0053] The third aspect of the present invention provides an application of the ultra-high molecular weight polyethylene fiber provided in the first aspect or the ultra-high molecular weight polyethylene fiber prepared by the preparation method provided in the second aspect in textiles.

[0054] The above-mentioned ultra-high molecular weight polyethylene fiber can ensure the tensile strength and anti-creep performance of the fiber while ensuring a thin diameter. The fiber length changes little over a long period of time, has a better positioning effect, and can be better applied to textiles, especially cables.

[0055] Preferably, the cable is a mooring cable and / or a fishing net cable. Based on the above properties, the fiber can be better applied to mooring cables and / or fishing net cables.

[0056] According to a particularly preferred embodiment of the present invention, there is provided a method for preparing an ultra-high molecular weight polyethylene fiber, comprising the following steps:

[0057] (1) mixing ultra-high molecular weight polyethylene powder, solvent I, a solubilizing agent and nano-magnetic particles and mechanically stirring the mixture for 3-24 hours to obtain a suspension;

[0058] The nanomagnetic particles are selected from at least one of manganese zinc ferrite, ferroferric oxide and magnetic polystyrene; the solubilizing agent is selected from at least one of polyethylene glycol, sodium xylene sulfonate, sodium p-toluene sulfonate, polysorbate and ethanol; the solvent I is selected from at least one of paraffin oil, mineral oil, decalin, tetralin and xylene; relative to 100g of the ultra-high molecular weight polyethylene raw material, the added amount of the nanomagnetic particles is 1-10g, the added amount of the solubilizing agent is 1-10g, and the added amount of the solvent I is 2-150g.

[0059] (2) introducing a mixture of an initiator, a coupling agent and paraffin oil into the suspension through a metering pump, and then spinning, and obtaining primary jelly filaments through pre-stretching (stretching ratio is 3-6 times) and cooling (temperature is 0-20° C., time is 3-10 seconds);

[0060] The initiator is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide and diisopropyl peroxydicarbonate; the coupling agent is selected from at least one of vinyl silane, organic titanate and acryloxy silane; relative to 100g of the ultra-high molecular weight polyethylene raw material, the added amount of the initiator is 1-35g, and the added amount of the coupling agent is 1-35g;

[0061] (3) After removing the solvent and drying the nascent jelly fibers, the fibers are subjected to ultra-high molecular weight polyethylene fiber extraction by ultra-high heat stretching (temperature of 120-180°C, relative humidity of 20-80%, and stretching multiple of 8-20 times) in a magnetic field with a magnetic field induction intensity of 100-800 A / m.

[0062] The ultra-high molecular weight polyethylene fiber prepared by the above preparation method has good creep resistance and tensile strength at break, and has a smaller fineness.

[0063] The present invention will be described in detail below through examples. In the following examples, ultra-high molecular weight polyethylene powder was purchased from Shenzhen Teli New Material Technology Co., Ltd., with a molecular weight of 4.5 million (density of 0.98 g / cm 3 ), molecular weight is 3 million (density is 0.97g / cm 3 );Silane coupling agent was purchased from Dongguan Zhenming Chemical Co., Ltd. with the product number KH-560;Organic titanate was purchased from Guangzhou Soman Trading Co., Ltd. with the product number 403;Vinyl silane was purchased from Shandong Yuanjin New Materials Co., Ltd. with the product number YJ-2151;Methacryloxy silane was purchased from Shandong Huachen New Materials Co., Ltd. with the product number kh550;Polyethylene glycol was purchased from Jinan Aoxing Chemical Co., Ltd. with the product number PEG400;Silica nanoparticles were purchased from Bohuas Nanotechnology (Ningbo) Co., Ltd. with the product number Brofos-SiO2.

[0064] Crosslinking degree: measured by the method mentioned in GB / T 18474-2001.

[0065] Content of nanomagnetic particles: A fixed mass of ultra-high molecular weight polyethylene fibers is dissolved in decahydronaphthalene at 120-140°C, the solid phase is obtained after filtration, and the fixed phase is weighed after drying. The content of nanomagnetic particles in the fibers is calculated by the mass of the solid phase and the added ultra-high molecular weight polyethylene fibers.

[0066] The magnetization intensity of magnetic nanoparticles was measured at 298 K using a Lake Shore-7400 vibrating sample magnetometer at a maximum magnetic field intensity of 1 kOe (saturation magnetization).

[0067] Creep elongation: Using the hanging weight method, 1.5m long parallel fibers are placed in an environmental chamber for creep performance testing. The hanging weight is 20% of the single fiber breaking strength, the hanging time is 48h, and the test temperature is 50℃.

[0068] Tensile strength at break: measured using the method mentioned in GB / T 14344-2008.

[0069] Breaking tensile force: obtained by testing using the method mentioned in GB / T 14337-2008.

[0070] Fineness: The fiber density is tested by GB / T14335, and the fiber length is tested by GB / T14336. The fiber fineness is calculated by the detected density and length.

[0071] Example 1

[0072] (1) Ultra-high molecular weight polyethylene powder (molecular weight 4.5 million, molecular weight 0.98 g / cm 3 ), a mixed solvent of paraffin oil and mineral oil (mass ratio of 1:9), polyethylene glycol and ferrosoferric oxide (particle size of 57.6 nm, magnetization intensity of 33emu / g) were mixed in a mass ratio of 5:94:0.5:0.5 and then mechanically stirred to obtain a uniform suspension after stirring for 24 hours;

[0073] (2) introducing a mixture of dicumyl peroxide, vinyl silane and paraffin oil in a mass ratio of 2:2:8 into the suspension by a metering pump at a mass ratio of 100:10 (suspension: mixture of dicumyl peroxide, vinyl silane and paraffin oil), and then spinning, and pre-stretching and cooling treatment (temperature of 15°C, time of 5s) by a spinneret and a spinning box to obtain primary jelly filaments, with a pre-stretching multiple of 3 times;

[0074] (3) The nascent gel fibers are extracted with an extracting liquid to remove the solvent, dried, and then subjected to super-multiple hot stretching treatment in a magnetic field with a magnetic field induction intensity of 100 A / m. The super-multiple hot stretching treatment temperature is 120° C., the relative humidity is 20%, and the stretching multiple is 8 times. The ultra-high molecular weight polyethylene fibers are collected and prepared as follows: Figure 1 shown.

[0075] Example 2

[0076] (1) Ultra-high molecular weight polyethylene powder (molecular weight 4.5 million, molecular weight 0.98 g / cm 3 ), a mixed solvent of paraffin oil and mineral oil (mass ratio of 5:5), sodium xylene sulfide and manganese zinc ferrite nanocrystals (particle size of 52.9nm, magnetization intensity of 48emu / g) were mixed in a mass ratio of 40:59:0.5:0.5 and then mechanically stirred to obtain a uniform suspension after stirring for 12h;

[0077] (2) introducing a mixture of di-tert-butyl peroxide, methacryloxysilane and paraffin oil in a mass ratio of 0.5:0.5:9 into the suspension by a metering pump at a mass ratio of 100:10 (suspension: mixture of di-tert-butyl peroxide, methacryloxysilane and paraffin oil), and then spinning, and pre-stretching and cooling treatment (temperature of 0°C, time of 3s) by a spinneret and a spinning box to obtain primary jelly filaments, with a pre-stretching multiple of 6 times;

[0078] (3) The nascent gel fibers are extracted with an extracting liquid to remove the solvent, dried, and then subjected to ultra-high heat stretching treatment in a magnetic field with a magnetic field induction intensity of 800 A / m. The temperature of the ultra-high heat stretching treatment is 180° C., the relative humidity is 80%, and the stretching multiple is 20 times. The ultra-high molecular weight polyethylene fibers are collected.

[0079] Example 3

[0080] (1) Ultra-high molecular weight polyethylene powder (molecular weight 3 million, molecular weight 0.97 g / cm 3 ), a mixed solvent of decahydronaphthalene and tetrahydronaphthalene (mass ratio of 1:1), polysorbate 80 and magnetic polystyrene nanospheres (particle size of 66.4 nm, magnetization intensity of 21emu / g) were mixed in a mass ratio of 20:79:0.5:0.5 and then mechanically stirred to obtain a uniform suspension after stirring for 3 hours;

[0081] (2) introducing a mixture of diisopropyl peroxydicarbonate, vinyl silane and paraffin oil in a mass ratio of 0.8:0.8:8.4 into the suspension by a metering pump at a mass ratio of 100:10 (suspension: mixture of diisopropyl peroxydicarbonate, vinyl silane and paraffin oil), and then spinning, and pre-stretching and cooling treatment (temperature of 20°C, time of 10s) by a spinneret and a spinning box to obtain primary jelly filaments, with a pre-stretching multiple of 4 times;

[0082] (3) The solvent of the primary frozen gel fibers is removed by circulating hot air at 50°C. After circulating for 9 hours and drying, the fibers are subjected to ultra-high heat stretching in a magnetic field with a magnetic field induction intensity of 600 A / m. The temperature of the ultra-high heat stretching treatment is 150°C, the relative humidity is 50%, and the stretching ratio is 12 times. The ultra-high molecular weight polyethylene fibers are collected and obtained.

[0083] Example 4

[0084] (1) Ultra-high molecular weight polyethylene powder (molecular weight 3 million, molecular weight 0.97 g / cm 3 ), a mixed solvent of decahydronaphthalene, tetrahydronaphthalene and xylene (mass ratio of 4:5:1), ethanol and ferroferric oxide (particle size of 57.6 nm, magnetization intensity of 31emu / g) were mixed in a mass ratio of 30:69:0.5:0.5 and then mechanically stirred to obtain a uniform suspension after stirring for 24 hours;

[0085] (2) introducing a mixture of diisopropyl peroxide, vinyl silane and paraffin oil in a mass ratio of 0.6:0.6:8.8 into the suspension by a metering pump at a mass ratio of 100:10 (suspension: mixture of diisopropyl peroxide, vinyl silane and paraffin oil), and then spinning, and pre-stretching and cooling treatment (temperature of 18°C, time of 10s) by a spinneret and a spinning box to obtain primary jelly filaments, with a pre-stretching multiple of 4 times;

[0086] (3) The solvent of the primary frozen gel fibers is removed by hot air circulation at 70°C. After the circulation for 3 hours and drying, the fibers are subjected to ultra-high heat stretching in a magnetic field with a magnetic field induction intensity of 400 A / m. The temperature of the ultra-high heat stretching treatment is 160°C, the relative humidity is 60%, and the stretching ratio is 16 times. The ultra-high molecular weight polyethylene fibers are collected and obtained.

[0087] Example 5

[0088] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that in step (2), vinyl silane was replaced by organic titanate.

[0089] Example 6

[0090] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that in step (2), vinyl silane was replaced by a silane coupling agent.

[0091] Example 7

[0092] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that in step (2), dicumyl peroxide was replaced by potassium persulfate.

[0093] Example 8

[0094] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that polyethylene glycol was not added in step (1).

[0095] Example 9

[0096] Ultra-high molecular weight polyethylene fiber was prepared according to the method of Example 1, except that ferrosoferric oxide (particle size 57.6 nm, magnetization intensity 31 emu / g) was added together with diisopropylbenzene peroxide and vinyl silane in step (2).

[0097] Comparative Example 1

[0098] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that vinyl silane was not added in step (2).

[0099] Comparative Example 2

[0100] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that ferrosoferric oxide (particle size of 57.6 nm, magnetization intensity of 31 emu / g) was not added in step (1), and step (3) did not include magnetic field treatment.

[0101] Comparative Example 3

[0102] Ultra-high molecular weight polyethylene fiber was prepared according to the method of Example 1, except that ferrosoferric oxide was not added in step (1) and vinyl silane was not added in step (2).

[0103] Comparative Example 4

[0104] Ultra-high molecular weight polyethylene fiber was prepared according to the method of Example 1, except that dicumyl peroxide was not added in step (2).

[0105] Comparative Example 5

[0106] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that the ferrosoferric oxide in step (1) was replaced by silicon dioxide nanoparticles (particle size of 50 nm).

[0107] Comparative Example 6

[0108] Ultra-high molecular weight polyethylene fibers were prepared according to the method of Example 1, except that step (3) did not include magnetic field treatment.

[0109] like Figure 1 As shown, the electron microscope images of the ultra-high molecular weight polyethylene fibers obtained in Example 1 and Comparative Example 3 are magnified 500 times. It can be seen that compared with Comparative Example 3, the surface morphology of the ultra-high molecular weight polyethylene fibers obtained in Example 1 is relatively rough, indicating that a cross-linking reaction has occurred in the fibers.

[0110] like Figure 2 As shown in the figure, the creep elongation of the ultra-high molecular weight polyethylene fiber obtained in Example 1 and Comparative Example 3 at 50°C and different hanging weight times (12h, 24h, 36h, 48h) is measured. It can be seen from the figure that compared with Comparative Example 3, the creep resistance of the ultra-high molecular weight polyethylene fiber obtained in Example 1 is significantly improved, indicating that the interaction force between the fiber molecular chains is significantly improved. Moreover, the creep elongation of the fiber provided in Example 1 at different hanging weight times does not change much, indicating that the fiber performance is relatively stable.

[0111] The performance of the ultra-high molecular weight polyethylene fibers prepared in the examples and comparative examples was tested, and the test results are shown in Table 1.

[0112] Table 1 Performance of ultra-high molecular weight polyethylene fibers obtained in Examples and Comparative Examples

[0113]

[0114] It can be seen from Table 1 that, compared with the comparative example, the ultra-high molecular weight polyethylene fiber obtained by the preparation process in the embodiment not only has a lower creep elongation, but also has larger fiber tensile fracture and breaking force, and a smaller fiber fineness. This shows that the preparation process in the present invention can effectively improve the creep resistance and tensile fracture strength of the fiber, while not affecting the super-multiple hot drawing of the fiber, and it is easy to obtain a target fiber with a thinner diameter.

[0115] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An ultra-high molecular weight polyethylene fiber, It is characterized in that The fiber contains nano magnetic particles, and the cross-linking degree of the fiber is greater than or equal to 84.5wt.%.

2. The ultra-high molecular weight polyethylene fiber according to claim 1, It is characterized in that The crosslinking degree of the fibers is 84.5-97.5 wt.%, preferably 85-93 wt.%.

3. The ultra-high molecular weight polyethylene fiber according to claim 1 or 2, It is characterized in that The fiber fineness is less than or equal to 150D; preferably less than or equal to 100D.

4. The ultra-high molecular weight polyethylene fiber according to claim 1 or 2, It is characterized in that The content of the nano magnetic particles in the fiber is 1-5 wt.%.

5. The ultra-high molecular weight polyethylene fiber according to claim 1 or 2, It is characterized in that The particle size of the nanomagnetic particles is 50-200 nm, preferably 50-120 nm.

6. The ultra-high molecular weight polyethylene fiber according to claim 1 or 2, It is characterized in that The magnetization intensity of the nanomagnetic particles is 20-50emu / g; Preferably, the nano magnetic particles are selected from at least one of manganese zinc ferrite, ferroferric oxide and magnetic polystyrene.

7. A method for preparing ultra-high molecular weight polyethylene fiber, It is characterized in that The steps include: (1) spinning an ultra-high molecular weight polyethylene raw material in the presence of an additive and a solvent to obtain primary jelly filaments; The auxiliary agent contains nano magnetic particles, a coupling agent and an initiator; (2) After removing the solvent from the primary jelly filaments, they are subjected to a heat drawing treatment in a magnetic field.

8. The preparation method according to claim 7, It is characterized in that The step (1) comprises: S1: mixing the ultra-high molecular weight polyethylene raw material, the solvent and the nano-magnetic particles to obtain a suspension; S2: mixing the suspension, the initiator, the coupling agent and the solvent, and spinning the mixture to obtain primary jelly fibers.

9. The preparation method according to claim 7 or 8, It is characterized in that In step (1), relative to 100 g of the ultra-high molecular weight polyethylene raw material, the amount of the nanomagnetic particles added is 1-10 g, the amount of the initiator added is 1-35 g, and the amount of the coupling agent added is 1-35 g; Preferably, the magnetization intensity of the nanomagnetic particles is 20-50emu / g; Preferably, the nano magnetic particles are selected from at least one of manganese zinc ferrite, ferroferric oxide and magnetic polystyrene; The initiator is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide and diisopropyl peroxydicarbonate; The coupling agent is selected from at least one of vinyl silane, organic titanate and acryloxy silane; Preferably, in step (2), the magnetic field conditions include at least: a magnetic field induction intensity of 100-800 A / m; The conditions of the heat stretching treatment at least include: a temperature of 120-180° C., a relative humidity of 20-80%, and a stretching ratio of 8-20 times.

10. Use of the ultra-high molecular weight polyethylene fiber according to any one of claims 1 to 6 or the ultra-high molecular weight polyethylene fiber prepared by the preparation method according to any one of claims 7 to 9 in textiles; Preferably, the textile is a cable; Preferably, the cables are mooring cables and / or fishing net cables.

Citation Information

Patent Citations

  • Silane cross-linking modified ultra-high molecular weight polyethylene fiber preparation method

    CN103993479A